Implementation of the E-Letter Application in Inter-Agency Coordination within the Regional Secretariat of Buleleng Regency - D. Agusto Mahendra; A.A.N Eddy Supriyadinata Gorda (International Journal of Management Science and Information Technology, 2026)
This study aims to analyze the implementation of the E-Letter application in the coordination process among agencies within the Regional Secretariat of Buleleng Regency, as well as to identify the supporting and inhibiting factors in its implementation. This study holds significant relevance in supporting the government’s digital transformation agenda, particularly through optimizing the use of information technology to enhance the effectiveness of public administration. The research employs a qualitative approach, utilizing in-depth interviews, observations, and documentation studies, with data analysis conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the E-Letter application has been relatively effective and has contributed significantly to improving efficiency, speed, and accuracy in administrative correspondence processes. The results also reveal that communication, resources, disposition, and bureaucratic structure, as outlined in Edward III’s theory, play a crucial role in determining the success of the implementation. However, several challenges remain, including unstable internet connectivity, suboptimal system performance, limited integration with external parties, and uneven user training. These findings imply the need to strengthen digital transformation policies, particularly through improving technological infrastructure, enhancing application features, and developing human resource capacity. This study recommends the development of a more flexible and integrated system as a strategic step toward improving the quality of governance.